"Dual contrast mode" imaging of anatase TiO2(001) − (1 × 4) reconstructed surface using non-contact atomic force microscopy. (28th June 2019) - Katsube, Daiki; Abe, Masayuki
Abstract: Different imaging modes of anatase TiO2 (001) − (1 × 4) reconstructed surface obtained with non-contact atomic force microscopy are investigated. In addition to the three typical types of imaging mode (protrusion, hole, and neutral modes) previously reported, we obtained "dual contrast" mode images in which two different tip apex atoms provide contrast. The new imaging mode has two atomic rows that are acquired in different spatial resolutions.